2009
DOI: 10.1111/j.1365-2958.2008.06588.x
|View full text |Cite
|
Sign up to set email alerts
|

Sec6‐dependent sorting of fungal extracellular exosomes and laccase of Cryptococcus neoformans

Abstract: SummaryThe cell wall of pathogenic fungi such as Cryptococcus neoformans, provides a formidable barrier to secrete virulence factors that produce host cell damage. To study secretion of virulence factors to the cell periphery, sec6 RNAi mutant strains of C. neoformans were tested for virulence factor expression. The studies reported here show that SEC6 RNAi mutant strains were defective in a number of virulence factors including laccase, urease as well as soluble polysaccharide and demonstrated attenuated viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
143
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 56 publications
9
143
0
Order By: Relevance
“…Capsule polysaccharide is transported to the cell surface in vesicles via exocytosis, and it is clear that trafficking of polysaccharide and other virulence-related factors such as laccase is important for the virulence of C. neoformans (60,66,67). Our observations that deletion of VPS23 caused increased sensitivity to BFA and monensin, two intracellular trafficking inhibitors, and that these inhibitors reduce capsule size, are consistent with a contribution to proper trafficking (13).…”
Section: Discussionsupporting
confidence: 67%
“…Capsule polysaccharide is transported to the cell surface in vesicles via exocytosis, and it is clear that trafficking of polysaccharide and other virulence-related factors such as laccase is important for the virulence of C. neoformans (60,66,67). Our observations that deletion of VPS23 caused increased sensitivity to BFA and monensin, two intracellular trafficking inhibitors, and that these inhibitors reduce capsule size, are consistent with a contribution to proper trafficking (13).…”
Section: Discussionsupporting
confidence: 67%
“…These results strongly suggest the potential of these vesicular structures to modify the course of cryptococcal infections through their effects on host phagocytic cells. Fungal vesicles are apparently related to mammalian exosomes (58,64). In this regard, it is noteworthy that exosome preparations from dendritic cells are being investigated as potential anticancer vaccines (26).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcosis is currently the fourth leading cause of death in Africa and it is estimated to affect one million individuals worldwide each year (Park et al, 2009). C. neoformans is found in the environment, and serological studies have shown that infection is common even though disease is rare (Goldman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these vesicles may be involved in transport of virulence factors out of the cell. Indeed, extracellular vesicle secretion has been associated with cryptococcal virulence in an animal model of infection (Panepinto et al, 2009). …”
Section: Introductionmentioning
confidence: 99%